Perlindungan Hukum bagi Kreditor terhadap Jaminan Hak Tanggungan yang dinyatakan oleh Pengadilan tidak Mempunyai Kekuatan Hukum - Ica Hanuun Lituhayu; Nurjihad (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to find out the legal protection and legal remedies that can be tidaken by creditors against mortgage guarantees declared by the court to have no legal force. This study uses normative research methods with secondary data as well as legal regulations and a case approach. The provisions in Article 1131 of the Civil Code provide legal protection regarding the consequences of mortgage guarantees which are declared to be invalid, namely general guarantees. The legal action that can be tidaken by creditors is that if the debtor is in default, they can file a civil lawsuit against the debtor's other assets in accordance with the provisions of Article 1131 of the Civil Code and also file an additional claim for confiscation, namely confiscation of collateral (conservatoir beslag) based on the provisions of Article 227 paragraph (1) HIR. Recommendations that can be given in this research are the 5C principle needs to be carried out by banks to analyze before providing credit to their customers. The Indonesian National Land Office as an institution that issues Mortgage Rights Certificates and Land Ownership Certificates should be more careful, accurate and thorough in administering land rights.